A PRAGMATIC ANALYSIS OF ANAPHORIC EXPRESSIONS IN TENET MOVIE - Ronaldo Samosir; Ambalegin Ambalegin (Asosiasi dosen IDEBAHASA KEPRI, 2022)
The goal of this research is to investigate the anaphoric references in a movie entitled Tenet. The researchers adapted the theory of anaphoric reference by Mitkov to find the types of anaphoric reference in the utterances of the movie. This research applied descriptive qualitative research. The researcher used the observational method to collect data, the pragmatic identity method to analyze the data, and the descriptive narrative method to present the research result. The researchers revealed the twenty data experienced anaphoric reference; three zero anaphoric expressions, nine pronominal anaphoric expressions, three verb anaphoric expressions, one lexical noun phrase anaphoric expression, three adverb anaphoric expressions, and one noun anaphoric expression. pronominal anaphoric expression is the mostly frequent use in the Tenet movie.